Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s00455-021-10396-z
|View full text |Cite
|
Sign up to set email alerts
|

An International Commentary on Dysphagia and Dysphonia During the COVID-19 Pandemic

Abstract: COVID-19 has had an impact globally with millions infected, high mortality, significant economic ramifications, travel restrictions, national lockdowns, overloaded healthcare systems, effects on healthcare workers’ health and well-being, and large amounts of funding diverted into rapid vaccine development and implementation. Patients with COVID-19, especially those who become severely ill, have frequently developed dysphagia and dysphonia. Health professionals working in the field have needed to learn about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 94 publications
(115 reference statements)
0
27
0
Order By: Relevance
“…Similarly, one study [ 12 ] involved COVID-19 patients with mild (71.5%) and moderate (28.4%) severity and showed that 24 (20.6%) out of 116 patients suffered from dysphagia. Another study [ 19 ] found that 3 (14%) of the small preliminary dataset of 21 non-hospitalized patients presented with self-reported dysphagia. The disparity between the results of these studies and ours could be largely explained by the differences in sample size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, one study [ 12 ] involved COVID-19 patients with mild (71.5%) and moderate (28.4%) severity and showed that 24 (20.6%) out of 116 patients suffered from dysphagia. Another study [ 19 ] found that 3 (14%) of the small preliminary dataset of 21 non-hospitalized patients presented with self-reported dysphagia. The disparity between the results of these studies and ours could be largely explained by the differences in sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Old age was usually linked to greater ICU admission rates and mortality from COVID-19, particularly among those with comorbidities [ 19 ]. In the current study, the average age of participants happened to be in the mid-30 s, probably because we included less severe, non-ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies concerning voice disorders in the course of COVID-19 disease were mainly based on subjective methods of examination [ 8 , 9 , 10 ]. The use of instrumental methods of assessment in diagnosing dysphonia in COVID-19 patients, namely, videolaryngoscopy, fluoroscopy, fibro-optic laryngoscopy, was reported only by a few researchers [ 11 , 12 , 13 , 14 ]. Instrumental data on dysphonia after COVID-19 are not plentiful and only emerging now because of restrictions in the use of endoscopy at the outset of the pandemic [ 14 ].…”
Section: Introductionmentioning
confidence: 99%